Accuracy of a cow-side test for the diagnosis of hyperketonemia and hypoglycemia in lactating dairy cows. (December 2017) - Macmillan, K.; López Helguera, I.; Behrouzi, A.; Gobikrushanth, M.; Hoff, B.; Colazo, M.G.
Abstract: The objective of this study was to evaluate the use of a cow-side device (FreeStyle Precision Neo™) to diagnose ketosis and hypoglycemia based on measures of blood β-hydroxybutyrate (BHBA) and glucose. Eleven commercial dairy farms were visited and blood samples were taken from Holstein cows between 2 and 14 days in milk, yielding 441 samples for BHBA analysis and 308 samples for glucose analysis. Concentrations of BHBA and glucose were measured in two ways, 1) using the cow-side device with whole blood immediately after sampling and 2) serum samples analyzed with a standard laboratory assay (Animal Health Laboratory, University of Guelph, Canada). The accuracy of the device was determined by comparing the results to the laboratory method as well as the ability to diagnose ketosis (BHBA ≥ 1.2 mmol/L) and hypoglycemia (glucose < 2.5 mmol/L). The concordance correlation coefficient (CCC), Bland-Altman plot and Kappa coefficient were calculated to evaluate agreement between the 2 methods using SAS (version 9.3). The CCC was 0.92 for BHBA and 0.56 for glucose measurements. The 95% confidence intervals of the Bland-Altman plot encompassed 97% and 95% of the mean difference between methods for BHBA and glucose measurements, respectively. The Kappa coefficients were 0.78 for BHBA and 0.23 for glucose measurements. These results indicate that the cow-side device is accurate for rapid measurement of blood BHBA and diagnosis of ketosis on farms but is not accurate for measurement of blood glucose concentrations and diagnosis of hypoglycemia. Highlights: This study determined the accuracy of a cow-side device to quantify blood BHBA and glucose compared to a laboratory method. The device was able to accurately measure blood BHBA concentrations and diagnose ketosis in lactating dairy cows. The device was unable to accurately measure blood glucose concentrations and diagnose hypoglycemia.